Longitudinal Characteristics of Water Falling Films - Al-Salman, Kassim Y.; Kadhum, Mohammed Kh. (Basrah Journal for Engineering Sciences, 2008)
Falling liquid films have several engineering applications, and the study of these films is considered to be an important and essential aspect. This work aims to present an extensive experimental investigation and theoretical analysis to a gravity driven laminar sinusoidal falling water film over an inclined plate to study its main characteristics such as: wave profile, mean wave thickness, wavelength and wave velocity. Film characteristics were investigated for different inlet water flow rate ani inclination angles to obtain the relation of the wave flow characteristics with the variables taken in the study. The results show that average wave thickness increases with Reynolds number and also with the flow direction. Good agreement was obtained between the experimental data and the theoretical results. Also, the results agreed well with the results of previous investigations.